Cardiometabolic measures and cognition in early menopause - Analysis of baseline data from a randomized controlled trial. (August 2022) - Pal, Lubna; Morgan, Kelly; Santoro, Nanette F.; Manson, JoAnn E.; Taylor, Hugh S.; Miller, Virginia M.; Brinton, Eliot A.; Lobo, Rogerio; Neal-Perry, Genevieve; Cedars, Marcelle I.; Harman, S. Mitchell; James, Taryn T.; et al.
Highlights: Central adiposity, but not obesity as defined by body mass index, was associated with lower cognitive function, as reflected by scores on the Modified Mini Mental Status examination, in recently postmenopausal women participating in the KEEPS randomized controlled trial. Considering these findings, proactive and timely initiation of interventions aimed at mitigating central adiposity might lessen the pace of the global march towards cognitive dysfunction. Abstract: Objective: The relationships between cardiometabolic indices and cognition were examined in recently menopausal women. Methods: Cross-sectional analysis of baseline data from the KEEPS (Kronos Early Estrogen Prevention Study)-Cognitive ancillary study (n = 621). Cognitive performance was assessed by the Modified Mini Mental Status (3MS) score (primary outcome). Physical cardiometabolic indices included body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), and blood pressure (BP). Biochemical cardiometabolic indices included serum levels of high sensitivity C-reactive protein (hs-CRP), total cholesterol (TC), low-density lipoprotein (LDL-C), high-density lipoprotein (HDL-C), non-HDL (non-HDL-C), triglycerides (TG), fasting serum glucose (FSG), and insulin resistance (HOMA-IR). Socio-demographic variables included age, race/ethnicity, education, and lifestyle (physical activity, smoking). Central adiposity was defined as WC > 88 cm (>35 in) and WHR > 0.8. Separate stepwise multivariable analyses (GLM, ordinal logistic regression and logistic regression) assessed relationships between 3MS scores (as continuous, in tertiles and dichotomized at 90 respectively) with the measures of central adiposity (predictor variables); socio-demographic variables (age, time since menopause, race, educational status and lifestyle) and cardiometabolic variables (BP, lipids, FSG, HOMA-IR and hs-CRP) were examined as covariates. The final multivariable models included time since menopause, race, ethnicity, educational status, strenuous exercise, BMI ≥30 kg/m 2, non-HDL-C and hs-CRP as covariates. Due to the high collinearity between the two indices of central adiposity, within each analytic strategy, separate models examined the respective associations of WC > 88 cm and WHR > 0.8 with 3MS score. Results: On adjusted analyses, indices of central adiposity were independent predictors of significantly lower 3MS scores (p < 0.05). Consistency in this relationship was observed across the three different multivariable regression analytic approaches (GLM, ordinal and logistic regression). Conclusions: Among recently menopausal women, WC > 88 cm and WHR > 0.8 were associated with significantly lower cognitive function, as reflected by lower 3MS scores. The mechanisms that might explain the observed negative implications of central adiposity for cognitive function warrant further study.